The Genealogy of the Hammurapi Dynasty - Finkelstein, J. J.
I. Introduction and Text; BM 80328; II. The Genealogical List; III. The Four palū’s (lines 29-32); IV. The Purpose of the Text (lines 33-43); V. Summary. Postscript; copy and photos of BM 80328 on pp. 96-97.